Pozycjonowanie produktu na przykładzie wybranych systemów hotelowych - Jedlińska, Maja (Product Positioning on the Example of Selected Hotel Systems, 2008)
Hotel systems take advantage of STP marketing in segmenting guests, selecting target markets and positioning their offer. The latter component of STP marketing is quite specific since it is ingrained in the consumer's awareness. This particular element verifies efforts taken up by the company. In order to illustrate activities referring to positioning there were selected solutions applied in seven minor hotel systems originating in countries characterized by significant experience in the field of tourism economy development. Their positioning strategies were presented suggesting the implementation of these concepts in the Polish hotels system by means of imitation positioning application.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 145-157